(untitled) (Experimental biology, 2024)
The strain Caldanaerobacter subterraneus KAk with keratinase activity was isolated from the Zarkent geothermal springs. The KAk1 strain grows under anaerobic conditions at temperatures ranging from 55 to 85°C (optimum 65-70°C) and pH 4.5-9.0 (optimum 6.8). Under optimal conditions with glucose, the cells are observed mainly as single cells, in pairs, or in rare chains, and do not form endospores. However, when grown on merino wool, feathers, or under suboptimal conditions, the KAk strain cells show significant elongation and altered morphology: the cell length increases to 5-8 µm, and spore formation is observed. The KAk strain demonstrates the ability to effectively degrade feather keratin and merino wool at 65-70°C. The 16S rRNA gene sequence (1452 bp) of the KAk strain, analyzed using the BLASTn program against the GenBank database, showed a high degree of similarity with other strains of C. subterraneus. The similarity of the 16S rRNA gene sequence between strain KAk and C. subterraneus subsp. tengcongensis DSM 15242T is 98.5%, while the difference from other strains of this species is 1-1.5%. This study describes the physiological characteristics of the KAk strain and its keratinolytic activity in comparison with other representatives of the genus Caldanaerobacter.